2005
DOI: 10.1007/s10333-005-0006-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of USLE for the prediction of nutrient losses in soil erosion processes

Abstract: Soil erosion in agricultural fields affects not only land productivity but also water environment down stream. Many investigations have been made for the prediction of soil erosion processes. The Universal Soil Loss Equation (USLE) has been applied broadly for the prediction of average annual soil loss from upland fields. However, there are few reports concerning the prediction of nutrient (N, P) losses based on the USLE. Thus, the objective of this study is to propose the prediction equation of nitrogen and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 3 publications
0
13
0
1
Order By: Relevance
“…Many researches indicated that the losses of particulate nutrient components in surface runoff from upland fields were much higher than dissolved ones, and sediment and suspended solids transported the nitrogen and phosphorus components (Mihara et al 2005;Ide et al 2008). Therefore, convenient erosion and sediment models can apply to doi: 10.2166/wst.2010.092 predict P losses.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches indicated that the losses of particulate nutrient components in surface runoff from upland fields were much higher than dissolved ones, and sediment and suspended solids transported the nitrogen and phosphorus components (Mihara et al 2005;Ide et al 2008). Therefore, convenient erosion and sediment models can apply to doi: 10.2166/wst.2010.092 predict P losses.…”
Section: Introductionmentioning
confidence: 99%
“…The most important consequence of erosion is sediment yield from the watershed, which causes siltation of canals, loss of storage volume in reservoirs, nutrient pollution, flooding, etc. (Vanoni 1982;Morgan et al 1998;Mihara et al 2005;Sadeghi et al 2007a). This affects not only the downstream environment, but also the socioeconomic development of the entire region.…”
mentioning
confidence: 99%
“…USLE sudah lama digunakan dan terus digunakan pada berbagai kasus. Di beberapa negara, integrasi USLE dan GIS telah digunakan untuk perencanaan dan perumusan konservasi tanah untuk pertanian, misalnya di Amerika bagian barat (Renard et al, 1991), di Denmark (Olsen et al, 1998), di Jepang (Mihara et al, 2005), di Turki (Baskan et al, 2009), di India (Bera, 2017), di Afrika Selatan (Smith, 1999) dan di Malaysia (Baban et al, 2001).…”
Section: Latar Belakangunclassified